2018
DOI: 10.1007/s00264-018-4143-0
|View full text |Cite
|
Sign up to set email alerts
|

Spine challenges in mucopolysaccharidosis

Abstract: Bracing is a viable treatment strategy in thoracic lumbar kyphosis and can obtain good clinical results at medium terms follow-up even if kyphosis deformity remains in radiographs. Surgical treatment is effective in severe evolving cases both at cervical and thoracic lumbar level, main difficulties arose from unavailability of dedicated instrumentation in very young patient, as even smallest devices available are often too big.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 39 publications
0
29
0
1
Order By: Relevance
“…Развитие ортопедической патологии, в том числе и патологии позвоночника, следует рассматривать в контексте ортопедических осложнений [11][12][13]. Это выражается в гипермобильности лучезапястных суставов, контрактурах крупных суставов в сочетании с туннельными синдромами, что проявляется проблемами самообслуживания и низким качеством жизни.…”
Section: обоснованиеunclassified
“…Развитие ортопедической патологии, в том числе и патологии позвоночника, следует рассматривать в контексте ортопедических осложнений [11][12][13]. Это выражается в гипермобильности лучезапястных суставов, контрактурах крупных суставов в сочетании с туннельными синдромами, что проявляется проблемами самообслуживания и низким качеством жизни.…”
Section: обоснованиеunclassified
“…Anterior beaking of the inferior aspect of the vertebral body is common in MPS I, while patients with MPS IV show anterior beaking of the midpoint of the vertebral body. However, it is still difficult to determine the type of MPS only by the shape of the vertebral deformity [49]. Thoracolumbar kyphosis causes sagittal imbalance accompanied by thoracic lordosis, pelvic anteversion, and lumbar hyper-lordosis, requiring flexed knee and hip joints to maintain standing balance [50].…”
Section: Thoracolumbar Kyphosismentioning
confidence: 99%
“…The effect of ERT or bone marrow transplantation on preventing spinal deformity is not confirmed and requires further examination of the natural history of kyphosis progression in MPS [24]. Abelin et al suggested using bracing to prevent kyphosis progression immediately after patients are able to maintain the sitting position [50], and Crostelli et al reported successful outcomes using braces in 15 patients with MPS I [49].…”
Section: Thoracolumbar Kyphosismentioning
confidence: 99%
“…Mucopolysaccharidosis involve the skeletal system and particularly the spine, with developing kyphosis at the thoracolumbar junction that can cause neurological symptoms, and dens hypoplasia with associated atlantoaxial subluxation that can cause myelopathy. Surgical treatment is effective in severe evolving cases both at the cervical and at the thoraco-lumbar level; the main difficulties arose from the unavailability of dedicated instrumentation in very young patients, as even the smallest devices available are often too big [20].…”
Section: Spinementioning
confidence: 99%